Awareness of medical students towards cancer - S., Radhika; Kareem, Hana Abdul; A., Najma R.; Bharadwaj, Ira (International Journal of Research in Medical Sciences, 2018)
Background: Cancer is the second leading cause of mortality worldwide. Amongst the cancers, the three leading cancers in India which causes high mortality and morbidity includes cervical cancer, breast cancer and upper aerodigestive tract carcinoma. High mortality and morbidity due to cancers can be reduced by preventive measures and early diagnosis of cancer, which can be achieved by creating awareness. Methods: A total of 337 medical students from 1st year to 4th year (1st year students-preclinical, 2nd year students-paraclinical and 3rd and 4th year students- clinical students) were included in this study and the results were analysed by descriptive statistics, Pearson’s Chi square test and paired ‘t’ test. Results: Out of 337 students, 120 were males, 204 were females and 13 students have not mentioned their gender. There was significant difference in knowledge of the students between pretest and posttest (following a short lecture) and amongst the preclinical, paraclinical and clinical students. Clinical students were found be more aware about the cancer compared to the preclinical and paraclinical students. Conclusions: Creating awareness to the medical students who are future doctors is the need of the hour. A short talk on cancer awareness can create a great impact on the awareness.